Governança multinível para o desenvolvimento regional: um estudo de caso do Consórcio Intermunicipal da Fronteira - Henrichs, Joanni Aparecida (2015)
Given the complexity that social and intergovernmental relations took in the contemporary scene, classical theories of integration aren’t able to show better understand of the inter-relationship claimed. In that nuance, the theory of multilevel governance presents a new perspective to try to understand the federative relations on its various levels (governmental and nongovernmental), especially considering the endogenous prism (starting from the local and regional portions). A reason for the study of multilevel governance is also shown when facing the complexity of decision- making processes in federative countries, clarifying the dilemma of collective action, encouraging the expansion of vertical and horizontal structures, gifted with a coherent and transparent decision-making process, providing, in this context, regional development. Therefore, the research aims to analyze the contribution, based on the study of the Intermunicipal Consortium of Frontier (CIF), of multilevel governance to regional development process in border regions. On the methodological aspect, it was adopted the case study strategy, qualitative approach, with descriptive and exploratory goals, accomplished through literature, documentary and field research, this one instrumented from semi-structured interviews with managers from CIF. As a result it was found that the multilevel governance contributes to the improvement of intergovernmental relations, in federative context, and serves as a link between intention and realization of regional development from the ground, enabling the democratic participation in the process. It was also found that the Intermunicipal consortium are important tools for coordination and work as a development strategy, not only for the municipalities involved, but also for the entire regional surroundings because they enable to plan, implement and manage shared public policies to solve common experience problems, giving visibility to the region over other governmental levels (state, federal and international) which favors the fluidity of multilevel governance primates.